2010
DOI: 10.1007/s12265-010-9243-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Mechanisms of the Anti-arrhythmic Effects of Omega-3 Fatty Acids

Abstract: Heart rhythm disorders, or arrhythmias, are a leading cause of morbidity and mortality worldwide. Omega-3 polyunsaturated fatty acids (ω3PUFAs), commonly found in fish oils and plant seeds, have recently emerged as potential anti-arrhythmic agents. The purpose of this review is to summarize the electrophysiological basis of the anti-arrhythmic properties of ω3PUFAs from clinical, animal, and cellular research. Evidence of the anti-arrhythmic effects of ω3PUFAs originated from epidemiological studies that corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 51 publications
0
33
0
1
Order By: Relevance
“…The consumption of EPA and DHA from fi sh oil increases atrial and ventricular EPA and DHA in membrane phospholipids ( 24,25,174 ). Several clinical trials have reported that 3 PUFA were able to i ) prevent SCD, ii ) prevent ventricular arrhythmia in patients with implantable cardioverter, iii ) lower occurrences of premature ventricular contractions, iv ) reduce heart rate, and v ) prevent atrial fi brillation ( 174,175 ). Studies in dogs showed anti-arrhythmic effects of EPA or DHA when administered during ischemia ( 176 ).…”
Section: Pufa Regulation Of Cardiomyocyte Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consumption of EPA and DHA from fi sh oil increases atrial and ventricular EPA and DHA in membrane phospholipids ( 24,25,174 ). Several clinical trials have reported that 3 PUFA were able to i ) prevent SCD, ii ) prevent ventricular arrhythmia in patients with implantable cardioverter, iii ) lower occurrences of premature ventricular contractions, iv ) reduce heart rate, and v ) prevent atrial fi brillation ( 174,175 ). Studies in dogs showed anti-arrhythmic effects of EPA or DHA when administered during ischemia ( 176 ).…”
Section: Pufa Regulation Of Cardiomyocyte Functionmentioning
confidence: 99%
“…Approximately 80-90% of sudden cardiac deaths are linked to ventricular arrhythmias, and arrhythmias are linked to control of heart contraction, a process involving electrophysiological mechanisms controlling muscle contraction ( 174,175,177,178 ). As such, studies with cardiomyocytes have focused on 3 PUFA regulation of Na + -, Ca +2 -, K + -channels, ion pumps, and the Na + /Ca +2 exchangers ( 173,175 ).…”
Section: Pufa Regulation Of Cardiomyocyte Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments on ion channels in cultured cells, on cardiac tissue in vitro, Langendorff preparations of explanted hearts, or using similar techniques investigating acute effects of EPA and/or DHA are reviewed elsewhere (De Caterina, 2011;Mozaffarian and Wu, 2011;Richardson et al, 2011;Savelieva et al, 2011). Of note, in such studies biologically active metabolites of EPA and DHA were defined, making the developments of more effective compounds a distinct possibility (e.g., Falck et al, 2011).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Underlying mechanisms have recently been reviewed (Richardson et al, 2011). The impression that EPA + DHA are primarily antiarrhythmic has been challenged by results of clinical studies, reporting that EPA and DHA did not reduce sudden cardiac death (SCD; Rauch et al, 2010).…”
Section: Introductionmentioning
confidence: 99%